The relationship between management practices and health facility performance: Evidence from low-resource, community-based facilities providing HIV services to key populations - Andrea Salas-Ortiz; Marjorie Opuni; José Luis Figueroa; Louis Masankha Banda; Alice Olawo; Spy Munthali; Julius Korir; Barbara Nyambura Thirikwa; Agatha Bula; Navindra Persaud; Sergio Bautista-Arredondo (PLoS ONE, 2025)
Management practices are deemed especially critical to performance in resource-constrained settings. However, empirical evidence is limited for community-based organizations (CBOs) that provide health services. We studied the association between management domains and performance among organizations delivering HIV services to key populations. We assessed organizational performance using cost efficiency, service volume, and outreach service quality. We collected data on 67 management practices from 45 CBOs in Kenya and Malawi and classified them into six domains—community engagement, financial management, operations management, people management, performance monitoring, and target setting. We calculated the scores for each domain, adjusting them for contextual characteristics to control for observed differences across organizations. Using ordinary least squares and quantile regression models, we explored the relationship between management and performance. We also estimated the relative contribution of each management domain to the explained variation of all performance indicators via a Shapley decomposition approach. Better management was associated with lower unit costs for antiretroviral therapy (ART) ($-1,124 pval<0.05), HIV testing services (HTS) ($-45 pval<0.05), and sexually transmitted infection (STI) screening, ($-30 pval<0.01). Higher management scores correlated positively with HTS volume (2,806, pval<0.001) and outreach quality (258, pval<0.05). Financial management was the most important domain, explaining 13–49% of performance indicator variation, performance monitoring explained 31% of outreach quality variation, and target setting explained 23–34% of service volume variation. These findings suggest that targeted capacity building in management practices, especially financial management, performance monitoring, and target setting, could improve the provision of HIV health services to key populations by CBOs.